Capital Adequacy Ratio Modeling - Lumbanraja, Thorman; Yulianto, Kompono Imam; Hakim, Luqman (International Journal of Membrane Science and Technology, 2023)
Intends to analyze the determinants of BOPO and its implications for CAR. This is important for banking management guidelines and society in general. The results are expected to find whether BOPO can mediate against CAR. Make a formula to maximize CAR value through BOPO as an indicator of efficiency and intervening variable. The object is a banking company on the Indonesia Stock Exchange (IDX) with a sample of 20 companies, a span of 8 years to form the 160 Observations data panel. There are two research models (Determinants of BOPO and Implications for CAR) which are integrated into one model using Eviews 9 software. In both analysis, a model selection test is required through the Chow Test, Hausman Test, and Lagrange Multiplier Test (LM). The results of the first model, an increase in INF, FS has an impact on a decrease in BOPO (efficient), results that are contrary to theory, LDR is positively correlated, NPL is negatively correlated, KI. The results of the second model, INF, LDR have a significant negative correlation with CAR, while KI, FS, NPL, and BOPO are significant according to theory. Significant BOPO intervening variables described by INFL, FS. It is hoped that it can help bank management in Indonesia to manage efficiency which has implications for CAR, considering that a bank is a place for people to secure their financial assets and trust institutions. Formulate a model for increasing CAR through BOPO efficiency as an intervening variable